Lecturers’ Attitudes toward Teaching Listening Comprehension (An analysis on English Study Program of STAIN Curup) - Hidayah, Jumatul (Universitas Islam Negeri Raden Intan Lampung, 2018)
Lecturer’s attitude in teaching listening are related with the availability of teaching material, their experience and capability and the strategy used and are regarded as success determinants of teaching itself. This article had a purpose toinvestigate lecturers’ attitudetowards teaching listening comprehension on English Study Program in STAIN Curup. This study was conducted in descriptive quantitative design. The participants of this study were 10 lecturers of listening comprehension lesson English study program of STAIN Curup. The data were collected by using questionnaires of Likert-scale formula and interview. The results showed that the lecturers’ attitude towards teaching listening comprehension is considered as Negative attitude.